Figures of speech : first amendment heroes and villains - Turner, William Bennett (PoliPointPress ; Distributed by Ingram Publisher Services, 2011)
Recounting controversial First Amendment cases from the Red Scare era to Citizens United, William Bennett Turner?a Berkeley law professor who has argued three cases before the Supreme Court?shows how we?ve arrived at our contemporary understanding of free speech. His strange cast of heroes and villains, some drawn from cases he has litigated, includes Communists, Jehovah?s Witnesses, Ku Klux Klansmen, the world?s leading pornographer, prison wardens, dogged reporters, federal judges, a computer whiz, and a countercultural comedian. This is a fascinating look at how the scope of our First Amendment freedoms has evolved and the colorful characters behind some of the most important legal decisions of modern times.?Turner tells fascinating stories of unlikely heroes and explains difficult legal issues clearly and concisely, educating and entertaining at the same time.??Elizabeth Farnsworth, The PBS News Hour.